Surgically assisted rapid maxillary expansion for complete bilateral cleft lip and palate rehabilitation: Technical features - Tovani-Palone, Marcos Roberto; Beja, Gabriela Benedini Strini Portinari; Perez-Faverani, Leonardo [UNESP]; Ramalho-Ferreira, Gabriel (Universidad Nacional de Colombia, 2017)
Cleft lip and/or palate are malformations with wide phenotypic heterogeneity, which require highly complex treatments in most cases. In turn, transverse maxillary deficiency is a common finding in individuals with complete cleft lip and palate, especially as a response to the restrictive effects of the primary reconstructive plastic surgeries. With this in mind, this study aims at presenting the technical description of the case of a patient with bilateral complete cleft lip and palate, who underwent surgically assisted rapid maxillary expansion, as well as discussing the relevant particularities.
Expansão rápida da maxila assistida cirurgicamente no tratamento reabilitador das fissuras bilaterais completas de lábio e palato: Particularidades técnicas
Keywords: Cleft lip; Cleft palate; Jaw (MeSH); Surgery